THE FREQUENCY OF TESTICULAR LESION IN ATERTIARY CARE CENTER - Prih Bashir; Noshaba Rahat; Humera Shahzad; Asma Jalbani; Farhana Zulfiqar; Bhawani Shankar (Baqai Journal of Health Sciences)
Objective: Testis is affected by both neoplastic and non-neoplastic lesions. Most commonly, patients present with scrotal swelling and pain. The objective of our research was to assess the histopathology of each testicular lesion.